Penggunaan Film Pendek Sebagai Bentuk Branding PT Sarinah - Ignatius Dwi Rezky Joel; Uud Wahyudin; Dedi Rumawan Erlandia (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This research was conducted to find out the message producer meaning towards PT Sarinah's branding in the short film